Peran Pusat Pertanggungjawaban Laba Dalam Sistem Pengendalian Manajemen - Ahmad Daffarid Yogasyah; Dhimas Ari Ardani; Moch. Novaldi Putra; Aryadewanto; Wiji (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the role of profit responsibility centers in the management control system as a key tool for improving the effectiveness and efficiency of company operations.A profit responsibility center is an organizational unit led by a manager with responsibility for managing revenue, costs, and achieving profit as a performance indicator. This study used a literature review method by reviewing various national and international scientific journals published between 2015 and 2025 and relevant to the research topic. The results indicate that the implementation of profit center responsibility accounting plays a crucial role in supporting the management control system by increasing accountability, transparency, and the ability to evaluate managerial performance. This system has been proven to help companies control costs, optimize profits, and improve the efficiency and effectiveness of resource management. Furthermore, the implementation of profit centers also strengthens coordination between organizational units and encourages more objective decision-making based on financial data